Answer:
see explanation
Explanation:
The remainder theorem states that if f(x) is divided by (x - h)
The the remainder is f(h)
(a)
Given f(x) is divided by (x - 1) then remainder is f(1), thus
f(1) =
+ 1³ + 2(1)² + a + b = 7, that is
1 + 1 + 2 + a + b = 7
4 + a + b = 7 ( subtract 4 from both sides )
a + b = 3 ← as required → (1)
(b
Given f(x) is divided by (x + 2) then the remainder is f(- 2), thus
f(- 2) =
+ (- 2)³ + 2(- 2)² + 2a + b = - 8, that is
16 - 8 + 8 + 2a + b = - 8
16 + 2a + b = - 8 ( subtract 16 from both sides )
2a + b = - 24 → (2)
Multiply (1) by 2
2a + 2b = 6 → (3)
Add (2) and (3) term by term to eliminate the term in a
3b = - 18 ( divide both sides by 3 )
b = - 6
Substitute b = - 6 into (1)
a - 6 = 3 ( add 6 to both sides )
a = 9
Thus a = 9 and b = - 6